Kontribusi Sosialisasi Lazis NU Kota Yogyakarta terhadap Perilaku Muzakki dalam Menunaikan Zakat - Sya'adi, Nur; Pratomo, Dimas (Tapis: Jurnal Penelitian Ilmiah, 2019)
The socialization of a procedure for collecting zakah is very important given to the Zakah Agency to carry out its management effectively and efficiently. This study examines the performance of Zakah, Infaq, Shodaqoh Agency of Nahdlatul Ulama (LAZIS NU) of Yogyakarta, where the zakah availability reaches 4.3 billion Rupiah per year, however, in reality, the LAZIS NU of Yogyakarta is only able to compile zakah as much 135 million Rupiah per year. This study tries to analyze how does the management and socialization of LAZIZ NU of Yogyakarta in running out its duty. The type of this research is a descriptive qualitative study by using an interactive analysis model by means of the inductive method. Based on the research results the implementation of the LAZIS NU's socialization Yogyakarta did not quite maximal, this was caused by the lack of socialization, the lack of human resources in conducting the socialization. That condition brought the funds raised were still far from the expectation. By this reason, the concrete action needs to be implemented related to fix those problems. The managerial must continuously improve programmed evaluations so that all activities can be controlled and easily evaluated.